1990
DOI: 10.1111/j.1440-1681.1990.tb01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Interaction of Ethanol and Kava Resin in Mice

Abstract: 1. The lipid soluble extract of the psychoactive beverage kava has hypnosedative properties which can be measured by the length of time that the righting reflex is lost. 2. Ethanol and the lipid soluble extract (kava resin) have been shown greatly to increase each others hypnotic action in mice. Ethanol also increases the toxicity of kava markedly. 3. This interaction of kava and alcohol has important clinical and social consequences since, in contrast to traditional usage, kava is now often taken in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 10 publications
(8 reference statements)
2
20
0
Order By: Relevance
“…141 Kava may interact with benzodiazepines; there is 1 controversial case report involving alprazolam. 142 While the consumption of large amounts of alco-hol has been noted to potentiate the actions of kava in mice, 143 administration of a standardized kava extract in a placebo-controlled, doubleblind study showed few adverse effects. 144 The possibility exists that concomitant administration may potentiate the action of other centrally mediated agents.…”
Section: 137mentioning
confidence: 99%
“…141 Kava may interact with benzodiazepines; there is 1 controversial case report involving alprazolam. 142 While the consumption of large amounts of alco-hol has been noted to potentiate the actions of kava in mice, 143 administration of a standardized kava extract in a placebo-controlled, doubleblind study showed few adverse effects. 144 The possibility exists that concomitant administration may potentiate the action of other centrally mediated agents.…”
Section: 137mentioning
confidence: 99%
“…Ethanol can enhance the hypnotic effect of kava-kava [96]. It can potentiate barbiturates and benzodiazepines [97].…”
Section: Potential Side Effects and Drug Interactionsmentioning
confidence: 99%
“…A synergistic effect was reported in mice using hypnotic doses of kava and alcohol (76). However, a clinical trial in 20 volunteers (77) given 100 mg of kava extract three times per day for 8 days tested the added effects of alcohol by adding ethanol on days 1, 4, and 8 (doses of alcohol were sufficient to achieve blood alcohol levels of 0.05%).…”
Section: Effects Of Dietary Supplementsmentioning
confidence: 99%